Effect of Long Term Vitamin D Supplementation on Biomarkers of Inflammation in Latino and African-American Subjects with Pre-Diabetes and Hypovitaminosis D - Sinha-Hikim, I.; Duran, P.; Shen, R.; Lee, M.; Friedman, T. C.; Davidson, M. B. (Hormone and Metabolic Research, 2015)
Low vitamin D levels are associated with minority subjects, the metabolic syndrome, and inflammation. The effect of vitamin D supplementation on markers of inflammation has not been well studied. The aim of the study was to evaluate the effects of high doses of vitamin D supplementation for 1 year on serum biomarkers of inflammation in Latino and African-American subjects with pre-diabetes and hypovitaminosis D. Latino (n=69) and African-American (n=11) subjects who had both pre-diabetes and hypovitaminosis D with a mean age of 52.0 years, a BMI of 32.7 kg/m2, and 70% of whom were females, were randomized to receive weekly doses (mean±SD) of vitamin D (85 300 IU±16 000) or placebo oil for 1 year. Serum levels of interleukin-6, tumor necrosis factor, highly sensitive C-reactive protein), plasminogen activator inhibitor 1, and insulin-like growth factor-1 were measured at baseline, 6, and 12 months. Serum 25-OH vitamin D levels of 22 ng/ml at baseline quickly rose to nearly 70 ng/ml in subjects receiving vitamin D and did not change in the placebo group. Two-way repeated measures ANOVA showed no differences between the 2 groups in any of the 5 selected parameters. High dose vitamin D supplementation for 1 year in minority subjects with pre-diabetes and hypovitaminosis D failed to affect serum biomarkers of inflammation.Clinical trial reg. no.: NCT00876928, clinicaltrials.gov
Keywords: vitamin D supplementation; inflammation; pre-diabetes; hypovitaminosis D